Marker-assisted pyramiding of soybean resistance genes RSC4, RSC8, and RSC14Q to soybean mosaic virus - Da-gang WANG; Lin ZHAO; Kai LI; Ying MA; Li-qun WANG; Yong-qing YANG; Yun-hua YANG; Hai-jian ZHI (Journal of Integrative Agriculture, 2017)
Soybean mosaic virus (SMV) is one of the major viral pathogens affecting soybean crops worldwide. Three SMV resistance genes, RSC4, RSC8, and RSC14Q, have been identified and mapped on soybean chromosomes 14, 2, and 13 from Dabaima, Kefeng 1, and Qihuang 1 cultivars, respectively. Soybean cultivar Nannong 1138-2 is widely grown in the Yangtze River Valley of China. In this study, crosses were made between Qihuang 1×Kefeng 1 and Dabaima×Nannong 1138-2. Ten simple sequence repeat (SSR) markers linked to three resistance loci (RSC4, RSC8, and RSC14Q) were used to assist pyramided breeding. Pyramided families containing three resistance loci (RSC4, RSC8, and RSC14Q) were evaluated by inoculating them with 21 SMV strains from China. Results indicated that the 10 markers can be used effectively to assist the selection of resistant individuals containing RSC4, RSC8, and RSC14Q A total of 53 F6 plants were confirmed to contain three homozygous alleles conferring resistance to SMV. Five F7 homozygous pyramided families exhibited resistance to 21 strains of SMV and showed desirable agronomic traits using dual selection. The strategy of pyramiding resistance gene derived from different varieties has practical breeding value in providing broad-spectrum resistance against the existing strains of SMV in China.